2020
DOI: 10.1101/2019.12.31.892018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotavirus Induces Intercellular Calcium Waves through ADP Signaling

Abstract: 26Rotavirus causes severe diarrheal disease in children worldwide. A hallmark of rotavirus 27 infection is an increase in cytosolic calcium in infected small intestine epithelial cells. However, 28 the underlying mechanism(s) of rotavirus-cell signaling remains incompletely characterized. Here 29 we show that rotavirus-infected cells produce paracrine signals that manifest as intercellular 30 calcium waves (ICWs); which are observed in both cell lines and human intestinal enteroids 31 (HIEs). Rotavirus ICWs ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Transcriptional readouts such as qPCR and RNA sequencing is the most accessible means by which to profile the nature of inflammatory responses in any in vitro model system. Especially, the comprehensiveness of RNA sequencing can permit detailed insights into the type of immune response, which is induced in organoids by triggers such as viral infection (Chang-Graham et al, 2020;Drummond et al, 2017;Lamers et al, 2020).…”
Section: Pattern Recognition and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional readouts such as qPCR and RNA sequencing is the most accessible means by which to profile the nature of inflammatory responses in any in vitro model system. Especially, the comprehensiveness of RNA sequencing can permit detailed insights into the type of immune response, which is induced in organoids by triggers such as viral infection (Chang-Graham et al, 2020;Drummond et al, 2017;Lamers et al, 2020).…”
Section: Pattern Recognition and Inflammationmentioning
confidence: 99%
“…A recently published virology study showed that the infection of intestinal organoids with rotavirus induced a paracrine ADP/ calcium signal through P2Y1 receptors that led to a deleterious inflammatory response (Chang-Graham et al, 2020). The suitability of an in vitro system for inflammation studies is therefore highly context dependent, with an advantage for organs-onchips where spatial control is important.…”
Section: Pattern Recognition and Inflammationmentioning
confidence: 99%